How Demographic Features and Attitudes of Student affect the Mathematics Performance of Students? With special reference to the Ordinary Level Students in Ratnapura Educational Zone in Sri Lanka - H.V.R.G Hathella; Hunuwala Malawarage Priyanath (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
The present study attempts to examine the effect of demographic characteristics and students' attitudes on the mathematics performance of Ordinary Level (OL) students in Sri Lanka. Data were collected from 110 students who sat for the 2019 OL examination, in Ratnapura Educational Zone in Sri Lanka. A structural questionnaire was used for data collection via a google form. ANOVA, t-tests, correlation tests, and descriptive statistics were employed for the data analyzing process. The results indicated that there are significant associations between mathematics performance and the demographic factors: residence, school type, parents’ educational level, and father’s occupation while the remaining factors; gender, mother’s occupation, family income, and some family members didn’t show significant relationships with mathematics performance. Results revealed a strong and significant association between mathematics performance and attitudes of students towards mathematics. Thus, the study provides empirical evidence which will support education officials, teachers, parents, and students to plan for achieving a higher performance of mathematics of OL students